FORMATION OF PERFORMANCE SKILLS IN THE CLASSROOM MAIN INSTRUMENT (PIANO) - O.V. Chebotarenko (Academy of Cognitive and Natural Sciences, 2006)
In clause conditions of development of pianistic performing skills of the future teachers of music are considered. The typology of performing skills and ways of their formation is offered.